5d+10e+7d+11e=

Simple and best practice solution for 5d+10e+7d+11e= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5d+10e+7d+11e= equation:


Simplifying
5d + 10e + 7d + 11e = 0

Reorder the terms:
5d + 7d + 10e + 11e = 0

Combine like terms: 5d + 7d = 12d
12d + 10e + 11e = 0

Combine like terms: 10e + 11e = 21e
12d + 21e = 0

Solving
12d + 21e = 0

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-21e' to each side of the equation.
12d + 21e + -21e = 0 + -21e

Combine like terms: 21e + -21e = 0
12d + 0 = 0 + -21e
12d = 0 + -21e
Remove the zero:
12d = -21e

Divide each side by '12'.
d = -1.75e

Simplifying
d = -1.75e

See similar equations:

| 804=600(1+0.17t) | | 7(6+2x)=20x | | 72+72(2z)-9(3Z-1)=4(2Z+4)-72(2Z) | | 3+5z-2=9z+9-3z | | x-3(5-x)=3*5 | | 20x-35=15 | | (3x)(y-7)=180 | | .27x+.02(5000-x)=600 | | x^4-2x^3+3x^2-5x+11= | | 5x+20(x-4)=145 | | 16m-12n-6+3n-9m= | | .45x+.4x=x-7.5 | | x+x+3007=7863 | | 2-7t=8-3t | | LN(y+1)=3 | | L=3H | | 64x^2+27x-64=0 | | 3x-(6x+18)=5-(12x-2) | | 4-5a=32-a | | 6(r-6)=-18 | | B+100=3P | | 2a*a+7a+5=0 | | (2+7)+3=2(7+3) | | x+x+3004=7886 | | 6(6+2x)=20x | | -10x+y=-9 | | x+x-3004=7886 | | 2y+2=-2 | | 2(R+6)=R+3R | | X-1=4.59 | | 4/5=x/80 | | x+x+7313=210355 |

Equations solver categories